Knowledge of reproductive health rights and its associated factors among Wolkite University undergraduate students, Wolkite, southern Ethiopia - Mohammed Seid Jemal; Zergaw Eskindir Demisie; Mosaa Kenzudin Assfa; Mossa Keyredin Nuriye; Yesgat Yibeltal Mesfin (Sciendo, 2022)
Objective: Reproductive health (RH) rights are the rights of all persons, regardless of age, sex, or other traits, and they have the freedom to make decisions about their sexuality and RH. However, there is limited information about Ethiopians' understanding of RH rights. Because little is known about the degree of knowledge and relevant predictors in the study area, this study was carried out to fill in the gaps.